Non-Academic Constructs of Thai and Filipino 21st Century Teachers in the Thai Movie “Teacher’s Diary” - Aljon Delmo Galang (IAIN MADURA, 2020)
Until the 21st Century, teachers are still seen in different constructs in countries such as the Philippines and Thailand. Though teachers' academic and non-academic roles are indispensably intertwined in the students' holistic development, the former roles are mostly the topic of query, clarification, and improvement, leaving the latter unclear. Nonetheless, the non-academic ones must be equally highlighted to educate the teaching force to achieve students' learning targets. Moreover, these roles lead to constructs, and these are seen in the modern representation of literary texts – films. In the Thai movie